2019
DOI: 10.1161/circimaging.119.009018
|View full text |Cite
|
Sign up to set email alerts
|

Association of Arsenic Exposure With Cardiac Geometry and Left Ventricular Function in Young Adults

Abstract: BACKGROUND: Arsenic exposure has been related to numerous adverse cardiovascular outcomes. The aim of this study was to investigate the cross-sectional and prospective association between arsenic exposure with echocardiographic measures of left ventricular (LV) geometry and functioning. METHODS: A total of 1337 young adult participants free of diabetes mellitus and cardiovascular disease were recruited from the SHFS (Strong Heart Family Study). The sum of inorganic and methylated arsenic concentrations in ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…7). Establishing this causal mechanism clarifies observational associations of iAS exposure and cardiac remodeling in humans independent of hypertension, and it stimulates further investigations not only upstream of NFAT activation, but also in the context of other environmental exposures and CVD endpoints (11).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…7). Establishing this causal mechanism clarifies observational associations of iAS exposure and cardiac remodeling in humans independent of hypertension, and it stimulates further investigations not only upstream of NFAT activation, but also in the context of other environmental exposures and CVD endpoints (11).…”
Section: Discussionmentioning
confidence: 65%
“…Recent findings from a multistate cohort study in an American population with a low burden of CVD risk factors show that individuals exposed to iAS exhibit altered left ventricular geometry (11). Although these results highlighted stronger associations among participants with preexisting hypertension, the association was also present without hypertension, suggesting that iAS exposure may directly promote cardiac remodeling (11). Previously, our laboratory reported that a 4-wk exposure to 1,000 μg/L iAS may impart sex-disparate effects on the heart (12).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have proved that long‐term exposure to As via contaminated drinking water, diet, or air can cause a variety of adverse health effects in humans. Apart from typical dermal changes, 2 multiorgan system damages, such as respiratory, 3 digestive, 4 urinary, 5 cardiovascular, 6 immune systems 7 and many other harmful effects also have been demonstrated. Among them, the liver, as the primarily metabolic and detoxifying organ, is already confirmed as a susceptible toxicity target to arsenic 8 .…”
Section: Introductionmentioning
confidence: 99%
“…2016 ). Chronic exposure from contaminated drinking water was linked to ventricular wall thickness and hypertrophy in young adults ( Pichler et al. 2019 ).…”
Section: Examples Of How the Kcs May Produce CV Dysfunction And Diseasementioning
confidence: 99%